(untitled) (International Seven Journal of Health Research, 2024)
Despite being feared, Brazilian venomous snakes can be reservoirs of important resources of medicinal interest, since the venoms of these animals have an invaluable potential for biologically active substances found in nature. Pharmacological and biochemical studies carried out in recent decades have shown the diversity of proteins with enzymatic activity, toxins, peptides, bioactive amines, among other compounds in snake venoms. The aim of this literature review was to describe the pharmaceutical biotechnological potential of Brazilian snake venom and to demonstrate the importance of these toxins and their pharmacological derivatives for public health. Since 1894, when they were studied by Vital Brazil, molecules derived from Brazilian snake venom have shown significant biological activity. These molecules have been proven to be efficient antimicrobial, antifungal and antiprotozoal agents, mainly due to their activity as serine proteases, hyaluronidases, L-amino acid oxidases (LAAO) and acetylcholinesterases, among other well-known substances. Brazilian snake venoms have thus been the target of a series of studies, which have borne excellent fruit, for example in the development of various drugs, such as Captopril®, which is derived from a peptide isolated from the venom of Bothrops jararaca, and fibrin sealant, derived from molecules in the venom of Crotalus durissus terrificus associated with cryoprecipitate from the blood plasma of buffaloes. With the analysis of biotechnologies applied to various molecules with the capacity for pharmacological, biologically active action, it is clear that this field is vast for new research and due to the great diversity of compounds in snake venoms. Certainly, as research progresses, new biologically active drugs derived from snake venom should become available for use and benefit of the population. Thus, studies related to the chemical composition of snake venoms should be encouraged, as well as those related to their pharmaceutical biotechnological potential.